A Qualitative Study on the Factors which Motivate Experienced Kwa-Zulu Natal Runners to Participate in Marathons - O'Byrne, Bianca (The IIE, 2020)
Introduction: Motivation and marathon running are interrelated because a marathon runner has to adopt training habits and lifestyle behaviours that goes beyond the recreational behaviour of individuals that run for a hobby. Purpose: The aim of this study was to describe the factors which motivate experienced runners to participate in marathons. Problem: The present study investigated the qualitative gap in the existing body of literature on the motivational factors in experienced runners and how these factors influence them to participate in marathons. Methodology: A semi-structured interview was constructed with three experienced runners (who have completed more than five marathons). A thematic analysis was then performed to examine the perspectives from each participant. Results: The findings indicated that experienced runners were mainly motivated to participate in marathons by their need to complete a marathon, the “runners high”, achieving personal marathon goals, sustainability to participate, and participation in the sport. Implications: These findings encourage further research on motivational factors of the different experienced runner levels to get a better understanding on the various motivational factors that could occur.
Keywords: Motivation; Experienced runner; Participation; Marathon